2020
DOI: 10.25259/sni_218_2019
|View full text |Cite
|
Sign up to set email alerts
|

Nerves transfers for functional hand recovery in traumatic lower brachial plexopathy

Abstract: Background: Distal nerve transfers are an innovative modality for the treatment of C8-T1 brachial plexus lesions. The purpose of this case series is to report the authors’ results with hand restoration function by nerve transfer in patients with lower brachial plexus injury. Methods: Three consecutive nerve transfers were performed in a series of 11 patients to restore hand function after injury to the lower brachial plexus: brachialis motor branch to anterior interosseous nerve (AIN) and supinator branch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Fifteen months postoperatively, the patient regained MRC grade 3 strength of the FPL and FDP [20] . In a case series of 4 patients written by Ray et al, all patients with brachial plexus injuries who received brachialis to AIN transfers regained grip strength, and 3/4 regained at least partial pinch strength [21] . All patients met at least MRC grade 3, with 3/4 patients recovering MRC grade 4 function of the FPL and FDP [21] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen months postoperatively, the patient regained MRC grade 3 strength of the FPL and FDP [20] . In a case series of 4 patients written by Ray et al, all patients with brachial plexus injuries who received brachialis to AIN transfers regained grip strength, and 3/4 regained at least partial pinch strength [21] . All patients met at least MRC grade 3, with 3/4 patients recovering MRC grade 4 function of the FPL and FDP [21] .…”
Section: Discussionmentioning
confidence: 99%
“…In a case series of 4 patients written by Ray et al, all patients with brachial plexus injuries who received brachialis to AIN transfers regained grip strength, and 3/4 regained at least partial pinch strength [21] . All patients met at least MRC grade 3, with 3/4 patients recovering MRC grade 4 function of the FPL and FDP [21] . Hawasli et al reported a detailed case of a patient who received a brachialis to AIN transfer after a complete C7 spinal cord injury [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Esto puede hacerse con transferencias nerviosas o tendinosas. Estudios recientes 35,36 han demostrado buenos resultados de las transferencias nerviosas de ramas del braquial para los nervios interóseo anterior y pronador redondo, o del supinador para el nervio interóseo posterior en caso de ser necesario. 3) Lesión global del plexo preganglionar: son las lesiones traumáticas del plexo, de peor pronóstico.…”
Section: Reconstrucción Secundariaunclassified
“…The treatment aims to restore a functional grip and fist either with nerve or tendon transfers. Recent studies 35 36 have shown good outcomes after transfers of the branch to the brachialis (musculocutaneous nerve) to the anterior interosseous nerve and pronator teres branch or from the supinator to the posterior interosseous nerve if necessary.…”
Section: Treatmentmentioning
confidence: 99%